Las incidencias del art. 643 núm. 15 del Código Orgánico Integral Penal en la sustanciación del procedimiento expedito en violencia contra la mujer o miembros del núcleo familiar. - Herembás, Vanessa P. (2022)
The present report has been guided based on the main objective has been to determine the incidences of article 643 numeral 15 of the Comprehensive Criminal Organic Code in the substantiation of the expedited procedure in violence against women or members of the family nucleus in order to verify if the expert reports in the criminal process they have the same effects in the absence of the respective support by the subscribers in the single hearing. From the review and analysis of the Ecuadorian doctrine and legislation, through the compilation of bibliographic information on the principles, guarantees and rights that are enshrined in the Constitution of the Republic, to contrast with the attributes that the test must have in criminal proceedings so that it favorably affects legal certainty. Regarding the methodology, the study was carried out according to the qualitative approach, through the type of descriptive research, applying the inductive, deductive, analytical, synthetic methods, with the application of the documentary analysis and interview techniques. Reaching in this way, as results that, in the absence of the testimony of the expert to support the expert report in cases of violence against women and members of the family nucleus, rights and constitutional guarantees of the accused are violated, specifically due process, rights of protection, right to defense, legal certainty and effective judicial protection.